Pengembangan Model Aplikasi Ujian Online Siswa Berbasis Website Menggunakan Metode PIECES - Sari, Meri Mayang; Iskandar, Dedi; Supriyanti, Dedeh; Panjaitan, Nice Cleveronica Elizabeth; Firdaus, Febby Cahya (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2025)
The rapid advancement of information technology compels educational institutions to adopt digital-based systems to enhance the efficiency and effectiveness of learning and assessment processes. This study aims to design and develop a web-based online examination system at SMK Al Hikma. The system is expected to provide a solution to the limitations of conventional paper-based exams, which are time-consuming, prone to human error, and inefficient in terms of scoring. The system development method used is prototyping, with requirements analysis based on the PIECES framework (Performance, Information, Economic, Control, Efficiency, and Service). The system is built using PHP programming language and MySQL as the database. Testing is conducted using the black-box method. The results of the study indicate that the developed system improves time efficiency, reduces operational costs, and enhances the accuracy of exam results.